The rise of the ruling reptiles and ecosystem recovery from the Permo-Triassic mass extinction - Ezcurra, Martin Daniel (2018)
One of the key faunal transitions in Earth history occurred after the Permo-Triassic mass extinction (ca 252.2 Ma), when the previously obscure archosauromorphs (which include crocodylians, dinosaurs and birds) become the dominant terrestrial vertebrates. Here, we place all known middle Permian–early Late Triassic archosauromorph species into an explicit phylogenetic context, and quantify biodiversity change through this interval. Our results indicate the following sequence of diversification: a morphologically conservative and globally distributed post-extinction ‘disaster fauna’; a major but cryptic and poorly sampled phylogenetic diversification with significantly elevated evolutionary rates; and a marked increase in species counts, abundance, and disparity contemporaneous with global ecosystem stabilization some 5 million years after the extinction. This multiphase event transformed global ecosystems, with far-reaching consequences for Mesozoic and modern faunas.